Energy potential form municipal solis waste in Perlis - Nur Wahidah Mardhiah Zullkiplee (Penerbit Universiti Malaysia Perlis, 2011)
The amount of municipal solid waste (MSW) that generated in Perlis is about 205 tons/day. The existing landfill currently are not properly managed due to the limited land availability in this state. Alternatively, thermal treatment of MSW should be implemented in view of advantages in energy recovery. Solid wastes will combusted to generated energy by using this technology. A study was conducted to estimate the energy content of MSW based on its physical composition, bomb calorimeter and proximate analysis. From the characterization of MSW, the main components of Perlis MSW were found to be glass, paper and plastic, which made up approximately 64% of the MSW. Calorimetric analysis revealed that the average energy content of MSW based on its physical composition is 2954kcal/kg and the energy potentialassessed to be at 859kW/day. Calorific value that obtained from bomb calorimeter is 3890 kcal/kg and energy potential of MSW assessed to be at 1132kW/day. Based on the proximate analysis, the energy content is 3037kcal/kg and the energy potential assessed to be at 883kW/day. With this energy potential, it could be utilized as the electricity, in order to save amount of energy and cost save.